PENINGKATAN FUNGSI KESEHATAN LANSIA MELALUI PEMBEKALAN SIGAP OBAT (SIAP GUNAKAN DAN ANTISIPASI PEMAKAIAN OBAT) PADA SELANTANG - Lindawati Setyaningrum (LPPM Universitas dr. Soebandi, 2025)
Elderly individuals often experience difficulty in medication management, which has the potential to reduce their quality of life. Monitoring drug use and anticipating potential risks is very important in maintaining the healthy function of the elderly. Therefore, health promotion education regarding the